Analisis Faktor-Faktor Yang Mempengaruhi Audit Delay: Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2011-2015 - Yelma Yunita; Efrizal Syofyan (Universitas Negeri Padang, 2017)
This study aims to examine the factors that affect audit delay, ie firm size, profitability level, and size of public accounting firm (KAP). A sample of 144 manufacturing companies listed on the Indonesian Stock Exchange (BEI) in 2011-2015. The research data is obtained from the publication of financial report year 2011-2015, which then analyzed using SPSS version 15 for testing the research hypothesis. The result of hypothesis testing shows that firm profitability level and KAP size negatively affect audit delay, while firm size does not affect audit delay. Subsequent research on similar topics is expected to include other independent variables to complement the research model, such as extraordinary items, the complexity of company operations, and IFRS convergenceKeywords: audit delay, factors, manufacturing companies